Knowledge Management Practice : A Descriptive Study of the Insurance Industry - Minah, Japang (2003)
The main purpose of this study was to describe the elements of knowledge management activities within the insurance industry. Since Malaysia entered its knowledge-based economy many insurance companies have responded by leveraging heavily on its information and communications technologies (ICTs). This scenario described the efforts of insurance companies developing its knowledge assets. Moreover, the emerging fluctuations of Malaysian insurance and investment market have directly incorporated the idea of using knowledge and information as sources of differentiation strategy. The study done was based on Earl’s (1994) knowledge management model quoted from Prusak (1997). A survey was conducted among 11 insurances companies, which involved 110 full-time cross-departments insurances personnel. Additionally, a structured interview was carried out among three managers of human resource management in the insurance companies. The findings showed a significant effort of management on its knowledge assets which referred as those who were able to translate their knowledge and communicate them into tangible products such working ideas and procedures to provide quality products and services delivery. However, the study also found that organizational knowledge of the insurance businesses was not only located in people’ head. Some respondents rather view organizational knowledge as to the extent that insurance companies utilized its technologies such as knowledge networks, and knowledge based system in its organizational learning culture. This suggests that the insurance companies must provide considerable programs that can enhance its knowledge assets such as by developing sustainable approach to transfer individual knowledge to organizational knowledge. Furthermore, the study identified some challenging issues of managing knowledge within the insurance industry. In conclusion, the existing knowledge management practices in insurance business indirectly focused in creating innovative service culture supported by collaborative technologies to secure competitive advantage, sustainable marketing policies performance as well enhancing individual productivity by leveraging on knowledge assets in human resources. This research has provided the basis for future research on knowledge management practices.